Parents' knowledge and socio-demographic determinants toward child's restraint system use - Sepideh Harzand-Jadidi; Homayoun Sadeghi-Bazargani; Koen Ponnet; Milad Jamali-Dolatabad; Barbara Minuzzo; Amirreaza Kamrani; Mahdieh Abbasalizad-Farhangi; Fatemeh Bakhtari Aghdam; Leila Jahangiry (BMC, 2023)
Abstract Background Lack of protection or improper protection, is one of the most important reasons of child passenger's death and injury in traffic crashes. Based on what we see on the roads, Iranian children are unrestrained inside the car. The aim of this study was to investigate children restrained system (CRS) use rate, its socio-demographic determinants and parents' knowledge toward CRS use among Iranian parents. Methods Using multi-stage cluster sampling and direct in filed method of observation, the behavior of 700 children in cars was observed in the current cross-sectional study. Socio-demographic determinants and parents' knowledge, toward using the CRS were evaluated using questionnaires. The study was performed from July to August 2019 in Tabriz city, northwestern Iran. Results The rate of child safety seat (CSS) use was 15.1% CI 95%:(12.5%,18.0%), and the rate of booster use was 0.6%; CI 95%:(4.3%,8.0%). The majority of parents [e.g. 64.3%; CI 95%: (60.7%,67.9%)], had low knowledge about the use of CRS. The most important reasons for not using CRS was lack of laws and policies [e.g. 59.7%; CI 95%:(12.5%,18.0%)], lack of knowledge [e.g.59.6%; CI 95%:(57.9%, 63.3%)] and the high cost of CRS [e.g. 57.6%; CI 95%:(53.81%,61.2%)]. The most important predictors of not using CRS were the child's age, parental knowledge, and the socioeconomic status of the household (p < 0.05). Conclusions Most children did not have CRS. The parents with higher education and those with higher socioeconomic status had higher rate of CRS use. Based on the low rate of CRS use and poor parental knowledge about it, education of parents toward boosters use and benefits of using CRS, enforcing mandatory laws and ploicies for CRS use in Iran, and allocation of government subsidies to low-income families for purchasing CRS are suggeted as essential strategies to increase CRS use.